Northern Argentinian Andes: A Factory of Energy Territories - Silvina Cecilia Carrizo; Guillermina Jacinto (Revue de Géographie Alpine)
The northern Argentinian Andes are strategically positioned in the energy transition. In the province of Jujuy, solar and mining projects of diverse scale are multiplying. Initiatives aimed at satisfying small demands and reducing energy poverty focus their efforts on dispersed populations and low-income groups. Large-scale photovoltaic power plants in high mountain plains, and lithium mines in salt flats introduce profound impacts on local communities, and on landscapes of high cultural and natural value. The paper aims to explore the materialities of the energy transition in Andean spaces, examining experiences in progress in the province of Jujuy. The analysis puts research results obtained in fieldwork missions into perspective. Fieldwork has enabled contact with projects, constructions, actors, and energy strategies. Direct observation, semi-structured interviews, photographic records, and bibliographic review support the reflections on the materiality and spatiality of the projects. Diverse experiences co-evolve in the territories of Jujuy. For extractive, productive, and service purposes, they show the opportunities that open up in Jujuy, a factory of energy territories of variable geometry.